Soil Fertility Analysis using Microarthropod Diversity Index in Coffee-Based Agroforestry in Mount Ungaran, Indonesia - Psn Masruri Sulistiyanto Ari; Ilham Alkian; Rully Rahadian (BUMI: International Journal of Environmental Reviews, 2023)
The conversion of forest functions to plantation land results in decreased land function and ecosystem disruption. Coffee-based agroforestry is a management system that is considered capable of maintaining land functions and reducing the level of leaching of nutrients. This study uses the soil microarthropod diversity index to evaluate the soil fertility level in 2 types of coffee-based agroforestry in Mount Ungaran. Sampling was conducted in Banyuwindu to represent intensive land and Gonoharjo as non-intensive land. Microarthropod samples in the soil were analyzed using Pitfall traps and extracted using the Tullgren-Funnel method. Soil microarthropods from the sampling were identified in family-level taxa. The species diversity index was analyzed using the Hutcheson t-test and the Sorensen similarity index. Characteristics of organic composition showed that intensive land had a value of 17% lower than non-intensive land. Environmental characteristics of intensive land types tend to have lower pH and soil moisture values ​​than non-intensive land. The Shanon-Wiener diversity index analysis showed that soil microarthropods on the Intensive land type were H'= 2.08 and the Non-Intensive was H'= 2.30. Hutcheson's t-test showed that the diversity of soil microarthropods was significantly different with a significant value (p-value < 0.05), and the Sorensen similarity index value showed a similarity level of 52.17%. Based on the results of various analyses, it can be concluded that the intensive type of land has lower soil fertility than non-intensive land in the coffee agroforestry system in Mount Ungaran.